Mustard Greens Growth and Yield Caused by Liquid Organic Fertilizer in Peat Soil - Infitar Lifri Siregar; Faiz Barchia; Hasanudin Hasanudin (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2019)
Mustard is one type of leaf vegetable favored by the community because it tastes fresh and contains lots of vitamins A, B, and a little vitamin C. The large area of peatlands in Indonesia and the lack of mineral soils that can be used as agricultural land, make peatland use necessary. Peat is used for agricultural development, with the main limiting factor for growing media conditions that are not conducive to root development, especially land conditions that are saturated with water, react with acid, and contain organic acids at levels that can poison plants, so that some reclamation measures are needed for the land condition peat becomes more suitable for plant development. This study aims to determine the response to the concentration of liquid organic fertilizer (LOF) and its interaction on the growth of mustard greens (Brassica juncea L.) in peatlands. This research was conducted from April to May 2018 using a completely randomized design (CRD). The treatment given was a dose of LOF consisting of 0; 500; 1000; 1500; 2000 and 2500 L/ha. The variables observed included soil pH, plant height, number of leaves, above-ground fresh weight, below ground fresh weight, above-ground dry weight, and below-ground dry weight. The results of this study indicate that dosing of LOF has a significant effect on plant height, above-ground fresh weight, and above-ground dry weight. However, it did not have a significant effect on soil pH, leaf number, and below ground fresh weight and ground dry weight. The application of the highest LOF at 2500 L/ha was able to increase plant height by an average of 7.75 cm.